19 F MRSI of capecitabine in the liver at 7 T using broadband transmit–receive antennas and dual‐band RF pulses. (16th September 2015) - van Gorp, Jetse S.; Seevinck, Peter R.; Andreychenko, Anna; Raaijmakers, Alexander J. E.; Luijten, Peter R.; Viergever, Max A.; Koopman, Miriam; Boer, Vincent O.; Klomp, Dennis W. J.
<x xml:space="preserve">Abstract</x> Capecitabine (Cap) is an often prescribed chemotherapeutic agent, successfully used to cure some patients from cancer or reduce tumor burden for palliative care. However, the efficacy of the drug is limited, it is not known in advance who will respond to the drug and it can come with severe toxicity. 19 F Magnetic Resonance Spectroscopy (MRS) and Magnetic Resonance Spectroscopic Imaging (MRSI) have been used to non‐invasively study Cap metabolism in vivo to find a marker for personalized treatment. In vivo detection, however, is hampered by low concentrations and the use of radiofrequency (RF) surface coils limiting spatial coverage. In this work, the use of a 7T MR system with radiative multi‐channel transmit–receive antennas was investigated with the aim of maximizing the sensitivity and spatial coverage of 19 F detection protocols. The antennas were broadband optimized to facilitate both the 1H (298 MHz) and 19 F (280 MHz) frequencies for accurate shimming, imaging and signal combination. B1+ simulations, phantom and noise measurements showed that more than 90% of the theoretical maximum sensitivity could be obtained when using B1+ and B1− information provided at the 1H frequency for the optimization of B1+ and B1− at the 19 F frequency. Furthermore, to overcome the limits in maximum available RF power, whilst ensuring simultaneous excitation of all detectable conversion products of Cap, a dual‐band RF pulse was designed and evaluated. Finally, 19 F MRS(I) measurements were performed to detect 19 F metabolites in vitro and in vivo. In two patients, at 10 h (patient 1) and 1 h (patient 2) after Cap intake, 19 F metabolites were detected in the liver and the surrounding organs, illustrating the potential of the set‐up for in vivo detection of metabolic rates and drug distribution in the body. Copyright © 2015 John Wiley & Sons, Ltd.